Conclusion on the peer review of the pesticide risk assessment of the active substance rescalure. (20th February 2015) - ,; ,
Abstract: The conclusions of the European Food Safety Authority (EFSA), following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State Austria for the pesticide active substance rescalure, and the considerations as regards the application to include rescalure in Annex IV of Regulation (EC) No 396/2005, are reported. The context of the peer review was that required by Regulation (EC) No 1107/2009 of the European Parliament and of the Council. The conclusions were reached on the basis of the evaluation of the representative use of rescalure as an insecticide by mating disruption on citrus. The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Missing information identified as being required by the regulatory framework is listed.